2014
DOI: 10.1080/09747338.2014.921412
|View full text |Cite
|
Sign up to set email alerts
|

Minimal Realizations of Logic Functions Using Truth Table Method with Distributed Simplification

Abstract: In the conventional method, a truth table (TT) is prepared from the specified logic function. Then it is expressed as the sum of min terms corresponding to the rows in which 1 appears. Finally, this function is further reduced using the Boolean identities. Thus, all the simplifications are concentrated at one place after the TT. This procedure does not always lead to the minimal realization. This paper deals with the minimal realization of logic function using TT in which TT is reduced successively by one vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 5 publications
0
15
0
Order By: Relevance
“…Minimization protocols for the 5-bit Boolean functions of the combinatorial method make up a protocol library for the process of minimizing 5 ISSN 2226-3780 standard procedures, so the application of a separate protocol is reduced to carrying out one algebraic transformation.…”
Section: The Object Of Research and Its Technological Auditmentioning
confidence: 99%
“…Minimization protocols for the 5-bit Boolean functions of the combinatorial method make up a protocol library for the process of minimizing 5 ISSN 2226-3780 standard procedures, so the application of a separate protocol is reduced to carrying out one algebraic transformation.…”
Section: The Object Of Research and Its Technological Auditmentioning
confidence: 99%
“…In contrast to [7][8][9][10][11][12][13][14][15][16], in this paper, the object of solving the problem of minimizing a Boolean function is a combinatorial block-diagram with repetition, which allows to concentrate the minimization principle within the truth table of a given function. The peculiarities of the combinatorial method consist in greater informativeness of the process of solving the problem in comparison with the algebraic method of minimizing the function, due to tabular organization and the introduction of figurative calculus apparatus.…”
Section: Issn 2226-3780mentioning
confidence: 99%
“…The second option is to minimize the 5-bit logic function (9). At the first stage, sets of three blocks are identified that allow procedures for gluing and replacing of variables.…”
Section: Issn 2226-3780mentioning
confidence: 99%
See 2 more Smart Citations